Comparative analysis of lifestyle behaviors and dietary intake among obese and non-obese individuals following bariatric surgery: a secondary data analysis from 2020 to 2022 - Althumiri, Nora A.; Bindhim, Nasser F.; Aldabaeab, Abdulaziz E.; AlMousa, Norah; Aljabbary, Rugayah; Alumran, Arwa (Frontiers in Nutrition, 2023)
Objective: The aim of this research is to perform a comparative examination of lifestyle habits and dietary consumption between obese and non-obese subjects who have undergone bariatric surgery. This is done with the intent of investigating the disparities in obesity outcomes attributable to these elements.This study involves a secondary analysis of cross-sectional data obtained from the Sharik Diet and Health National Survey (SDHNS). To ensure a representative distribution of participants, the SDHNS employs a proportional quota sampling strategy, with stratification based on age, sex, and geographic location within Saudi Arabia's 13 administrative regions, utilizing the ZDataCloud® system for this purpose. The data, collected between 2020 and 2022 from over 15,000 participants, were screened to identify the eligible records of individuals who underwent bariatric surgery.Within the entire sample, a mere 5.0% (806 individuals) had undertook bariatric surgery, with females comprising 54% of this specific subgroup. The average age within this group was 38.85 years (SD 13.02) and range (18-87). Post-operative results showed that 33% of these individuals remained classified as obese. Utilizing the backward likelihood ratio regression model, it was determined that factors including age, decreased consumption of fresh juices and chicken, as well as current tobacco use, were significantly associated with persistent obesity.The findings of this study suggest an association between the non-obese group and healthier lifestyle choices, including the consumption of high-protein diets and fresh juices, alongside a decreased prevalence of smoking. These observations underscore the significance of maintaining a healthy lifestyle for positive weight loss outcomes following bariatric surgery.